Analisis Tingkat Kepuasan Pasien Terhadap Pelayanan Kefarmasian di Puskesmas Malawili Kabupaten Sorong - Aswitha Sari Suprihathin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Patient satisfaction is one of the factors that help improve the quality of health services. When a patient's experience after obtaining health services is compared to the patient's expectations, the resulting level of satisfaction can be measured. Finding out how satisfied Malawili Health Centre patients are with their pharmacological care was the motivation for this survey. In this descriptive study with a cross-sectional design, one hundred participants were surveyed between September and October 2023 at the Malawi Health Centre Pharmacy Services Department. Data was collected to measure the level of patient satisfaction through questions in the categories of tangible evidence (reliability), responsiveness, assurance, and empathy. SPSS software was used to analyse patient satisfaction levels. The results of the analysis of each dimension of patient satisfaction were as follows: tangibility 76.4%, reliability 82%, responsiveness 83.8%, assurance 86.7%, and empathy 89.35%. Meanwhile, the P values of the sociodemographic relationship test results and satisfaction levels were all > 0.05, including gender (0.000 < 0.1), age (0.208 > 0.1), education (0.673 > 0.1), occupation (0.000 < 0.1), and income (0.000 < 0.1).